Desarrollo de una propuesta para el uso eficiente de las aguas residuales provenientes del PTAR en Pharmetique Labs S.A. (2020)
In this project, a proposal is made in order to give efficient use to the water resources treated in the RWTP of the company Pharmetique Labs SA, having as its main purpose to reuse these waters in processes that do not involve the production process, reducing the concentration of phenolic pollutants from 0.32 mg/L to 0.002 mg/L to meet quality parameters and generate competitiveness at an environmental level for the company. For this, the tertiary treatment of ion exchange resins is selected at a theoretical level by means of a decision matrix, comparing it with other widely used treatments for the removal of phenols such as advanced ozone oxidation and carbon adsorption; analyzing the selection criteria for each of them. The evaluation of this treatment is carried out theoretically comparing the use of two types of resins where the results that are analyzed are the removal percentages, which range from 99.96% to 74.2% for Amberlyst A26 OH (strong anionic) and from 65.7% to 22.1% for Amberlite IRA-67 (weak anionic), depending on the variation in concentrations between 1 mg/L and 200 mg/L of the phenol pollutant; where, the effect of the initial concentration, the recirculation time and the pH of the sample is studied; and thus, the final concentration of phenols is determined at a theoretical level for the company Pharmetique Labs S.A., which is 0.000128 mg/L. Finally, it is proposed to implement an exchange column using strong anionic type resin such as Ambersep 900 OH, taking into account the design conditions and investment costs to reuse the treated water in pre-cleaning processes of the equipment in the syrup or emulsion manufacturing area, generating a positive environmental impact.